Cosatu after 40: Part 2: The implications of multi-sectoralism for COSATU’s centralised bargaining aspirations - Godfrey, Shane; Jacobs, Mario; Macun, Ian (New Agenda: SA Journal of Social and Economic Policy, 2026)
Until the reforms to labour legislation initiated in 1979, almost all the trade unions that formed the Congress of South African Trade Unions (COSATU), the National Council of Trade Unions (NACTU), and the Council of Unions of South Africa (CUSA) were excluded from participating in industrial councils. These unions had therefore pursued a plant-level collective bargaining strategy that enabled them to maximise their bargaining power and worker control. After the reforms, the new unions had to decide whether they would continue to bargain mainly at plant/enterprise level or participate in industrial councils. The option of bargaining at both levels was more or less excluded because it was so strongly opposed by employers.